Longitudinal Associations Between Adolescent Alcohol Use and Adulthood Sexual Risk Behavior and Sexually Transmitted Infection in the United States: Assessment of Differences by Race - Khan, Maria R. (American Public Health Association, 2012)
Objectives. We examined race differences in the longitudinal associations between adolescent alcohol use and adulthood sexually transmitted infection (STI) risk in the United States. Methods. We estimated multivariable logistic regression models using Waves I (1994–1995: adolescence) and III (2001–2002: young adulthood) of the National Longitudinal Study of Adolescent Health (n = 10 783) to estimate associations and assess differences between Whites and African Americans. Results. In adjusted analyses, adolescent alcohol indicators predicted adulthood inconsistent condom use for both races but were significantly stronger, more consistent predictors of elevated partnership levels for African Americans than Whites. Among African Americans but not Whites, self-reported STI was predicted by adolescent report of any prior use (adjusted odds ratio [AOR] = 1.47; 95% confidence interval [CI] = 1.00, 2.17) and past-year history of getting drunk (AOR = 1.53; 95% CI = 1.01, 2.32). Among Whites but not African Americans, biologically confirmed STI was predicted by adolescent report of past-year history of getting drunk (AOR = 1.68; 95% CI = 1.07, 2.63) and consistent drinking (AOR = 1.65; 95% CI = 1.03, 2.65). Conclusions. African American and White adolescent drinkers are priority populations for STI prevention. Prevention of adolescent alcohol use may contribute to reductions in adulthood STI risk.